2016
DOI: 10.1038/srep34530
|View full text |Cite
|
Sign up to set email alerts
|

Illusions of having small or large invisible bodies influence visual perception of object size

Abstract: The size of our body influences the perceived size of the world so that objects appear larger to children than to adults. The mechanisms underlying this effect remain unclear. It has been difficult to dissociate visual rescaling of the external environment based on an individual’s visible body from visual rescaling based on a central multisensory body representation. To differentiate these potential causal mechanisms, we manipulated body representation without a visible body by taking advantage of recent devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 38 publications
(50 reference statements)
3
52
2
Order By: Relevance
“…The finding that ownership promotes visual awareness provides an important new role for ownership in sensory processing and helps to explain the central role of body ownership in conscious awareness. We know from earlier studies that ownership can change the content of conscious perception in such ways as enhancing tactile acuity ( Haggard et al, 2003 ; Longo et al, 2008 ), calibrating proprioception ( Abdulkarim and Ehrsson, 2016 ; Botvinick and Cohen, 1998 ; Tsakiris and Haggard, 2005 ), and scaling visuospatial perception ( van der Hoort and Ehrsson, 2014 , van der Hoort and Ehrsson, 2016 ; van der Hoort et al, 2011 ). The fundamental advance made in this study is the demonstration that body ownership can affect the very presence of conscious perception, namely, visual awareness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that ownership promotes visual awareness provides an important new role for ownership in sensory processing and helps to explain the central role of body ownership in conscious awareness. We know from earlier studies that ownership can change the content of conscious perception in such ways as enhancing tactile acuity ( Haggard et al, 2003 ; Longo et al, 2008 ), calibrating proprioception ( Abdulkarim and Ehrsson, 2016 ; Botvinick and Cohen, 1998 ; Tsakiris and Haggard, 2005 ), and scaling visuospatial perception ( van der Hoort and Ehrsson, 2014 , van der Hoort and Ehrsson, 2016 ; van der Hoort et al, 2011 ). The fundamental advance made in this study is the demonstration that body ownership can affect the very presence of conscious perception, namely, visual awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that body ownership plays an important role in visual perception more generally, affecting how one sees the external world beyond one’s body ( Banakou et al, 2013 ; Haggard and Jundi, 2009 ; Linkenauger et al, 2013 ; van der Hoort et al, 2011 ). In particular, studies have shown that body size serves as a ruler in the size perception of objects in the external world, but only in the presence of ownership ( van der Hoort and Ehrsson, 2014 , van der Hoort and Ehrsson, 2016 ; van der Hoort et al, 2011 ). When participants experience body ownership of a small doll, other objects appear larger and farther away; conversely, ownership of a large artificial body makes other objects appear smaller and closer.…”
Section: Introductionmentioning
confidence: 99%
“…These delays may have been too long, such that any downregulation of the motor system could have 'worn off' by the cue to movement. Although we have no data on the duration of the after-effect of body disownership illusions, we know that the after-effects on limb ownership illusions [80] and full-body ownership illusions are quite longlived and can produce behavioural effects for many seconds after multisensory stimulation has stopped and the artificial body is no longer in view [18,81,82]. Lastly, it is also possible that the duration of visuotactile stimulation (13.5 seconds in experiment 1, 30 seconds in experiment 2 and 3) may have been too short to induce strong effects on later finger movement.…”
Section: Experimental Limitationsmentioning
confidence: 98%
“…However, the results of these experiments, in which interaction with the environment was required, might not be in keeping with an effect of body ownership on movement per se. For example, ownership of a differently-sized hand might alter object-directed action through scaling of the visual environment [16][17][18], altering the perceived spatial relationship between the body and the world, rather than acting upon the motor system directly. As such, whilst body ownership may be important for action, it is still unclear whether manipulating body ownership directly interferes with the generation or performance of movement.…”
Section: Introductionmentioning
confidence: 99%
“…The body representation is malleable: e.g., (Lackner, 1988;Ramachandran and Hirstein, 1998;de Vignemont et al, 2005;Ehrsson et al, 2005b;Longo et al, 2009a) Non-bodily objects can be embodied: e.g., (Botvinick and Cohen, 1998;Slater et al, 2008;Petkova et al, 2011a;Nishio et al, 2012Nishio et al, , 2018Ogawa et al, 2012;Guterstam et al, 2013Guterstam et al, , 2015Caspar et al, 2015;Kilteni et al, 2015;Ma and Hommel, 2015a;van der Hoort and Ehrsson, 2016;Aymerich-Franch et al, 2017a;Jazbec et al, 2017;Liepelt et al, 2017;Weser et al, 2017;Kondo et al, 2018a) 2. Embodiment can be evoked by mediated sensorimotor interaction Embodiment can be evoked by mediated: -visuotactile stimulation: e.g., D'Alonzo and Cipriani 2012; (Petkova and Ehrsson, 2008;Slater et al, 2008;Kilteni et al, 2012a;Maselli and Slater, 2013;Keizer et al, 2016;Krom et al, 2019) -visuomotor and proprioceptive cues: e.g., (Tsakiris et al, 2006;Dummer et al, 2009;Sanchez-Vives et al, 2010;Slater et al, 2010;Petkova et al, 2011a;Walsh et al, 2011;Kilteni et al, 2012b;Alimardani et al, 2013;Ma and Hommel, 2013;Maselli and Slater, 2013;…”
Section: The Body Representation Is Malleable and Can Include Non-bodmentioning
confidence: 99%